2019
DOI: 10.1186/s40634-019-0172-x
|View full text |Cite
|
Sign up to set email alerts
|

Capsular plication in the non-deformity hip: impact on post-operative joint stability

Abstract: Purpose and hypothesisThe aim of this study was to evaluate the hip joint range of motion after different capsular plication. The study hypothesis proposed that capsular plication after hip arthroscopy may reduce hip external rotation and thus prevent the hip joint instability created by arthroscopic capsulotomies.MethodsSix fresh frozen human cadavers were studied in the intact state (5 males, 1 females) for a total of 12 non-deformity hips tested. They were fixed to the operating room table using a custom-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Biomechanical studies support the correlation between hip capsular management and stability of the hip joint postoperatively and suggest closure of the capsule to preserve stability. 3,4,6,29,39 Some studies demonstrated that preservation of the iliofemoral ligament was critical to maintain native external rotation and anterior translation of the head of the femur, an important mechanism in protecting the hip from dislocating. 3,30,31,39 Other studies that evaluated the kinematics and torsional load of the hip joint concluded that the capsule should be routinely repaired in any hip procedure for patients with a predisposition to hip microinstability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanical studies support the correlation between hip capsular management and stability of the hip joint postoperatively and suggest closure of the capsule to preserve stability. 3,4,6,29,39 Some studies demonstrated that preservation of the iliofemoral ligament was critical to maintain native external rotation and anterior translation of the head of the femur, an important mechanism in protecting the hip from dislocating. 3,30,31,39 Other studies that evaluated the kinematics and torsional load of the hip joint concluded that the capsule should be routinely repaired in any hip procedure for patients with a predisposition to hip microinstability.…”
Section: Discussionmentioning
confidence: 99%
“…1,37,39,45,49 However, repair or plication of the capsule in patients with low risk of postoperative instability may be deleterious to hip range of motion without improving stability. 6,14,18,23 Prior clinical studies have reported mixed findings, possibly related in part to limited historical cohort sizes. The largest clinical study to date assessing the influence of capsular closure during a variety of arthroscopic hip procedures found no differences on multiple patient-reported outcomes between groups after adjustment for age, body mass index, sex, preoperative patient-reported outcomes, and degree of chondral damage.…”
mentioning
confidence: 99%
“…23,24 Others point to lower risk for arthritis development. 25,26 Skeptics of routine capsular closure cite the theoretical risk of over-constraint 27 and increased operative time with no proven benefits. 28 Past reviews have attempted to address the question of the best way to manage the capsule after hip arthroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Others point to lower risk for arthritis development 25,26. Skeptics of routine capsular closure cite the theoretical risk of over-constraint27 and increased operative time with no proven benefits 28…”
Section: Introductionmentioning
confidence: 99%